2007
DOI: 10.1038/ja.2007.79
|View full text |Cite
|
Sign up to set email alerts
|

Structure-activity Relationships of Neoechinulin A Analogues with Cytoprotection against Peroxynitrite-induced PC12 Cell Death

Abstract: Neoechinulin A, an alkaloid from Eurotium rubrum Hiji025, protected neuronal PC12 cells against cell death induced by peroxynitrite derived from SIN-1 (3-(4-morpholinyl)sydnonimine hydrochloride). In this study, we investigated the structure-activity relationships of neoechinulin A and a set of its analogues by using assays to measure anti-nitration and antioxidant activities and cytoprotection against SIN-1-induced PC12 cell death. The presence of the diketopiperazine ring was essential for both the antioxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
48
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 31 publications
3
48
0
Order By: Relevance
“…The presence of echinulin in the environment is not well documented however. In contrast to the negative effects of echinulin, neoechinulin has anti-oxidant properties (Yagi and Doi 1999) and protected PC12 cell lines, used in neurological research, against cell death by peroxynitrite (Kimoto et al 2007;Maruyama et al 2004). Visagie et al (2014a) emphasized that despite the existence of comprehensive ITS barcode reference databases, this marker is insufficient for identifying most Aspergillus, Penicillium and Talaromyces to species level in culture-independent surveys such as those of Amend et al (2010) and Adams et al (2013a;2013b).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of echinulin in the environment is not well documented however. In contrast to the negative effects of echinulin, neoechinulin has anti-oxidant properties (Yagi and Doi 1999) and protected PC12 cell lines, used in neurological research, against cell death by peroxynitrite (Kimoto et al 2007;Maruyama et al 2004). Visagie et al (2014a) emphasized that despite the existence of comprehensive ITS barcode reference databases, this marker is insufficient for identifying most Aspergillus, Penicillium and Talaromyces to species level in culture-independent surveys such as those of Amend et al (2010) and Adams et al (2013a;2013b).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the mechanism of cytoprotection by neoechinulin A apparently results from preventing cytotoxic events that are either downstream or independent of complex I dysfunction. We have found that neoechinulin A treatment can enhance the capacity of cells to produce NADH [1,2], which may be one factor underlying the cytoprotective mechanism. The requirement for the co-presence of neoechinulin A during MPP ϩ treatment to provide protection suggests that the antioxidant activity of neoechinulin A [1,2] and/or interaction with a cellular target may be responsible for the cytoprotection against MPP ϩ .…”
mentioning
confidence: 99%
“…No change in the absorption spectrum was observed when neoechinulin A was incubated with MPP ϩ in a physiological solution (PBS, pH 7.4) at 37°C overnight (data not shown), ruling out the possibility that neoechinulin A reacted with MPP ϩ and thereby chemically antagonized the neurotoxin. Previous studies indicated that pre-incubation with neoechinulin A for 12 hours was essential to render the cells resistant to peroxynitrite toxicity, and that once the cells had been fortified by neoechinulin A treatment, the presence of the alkaloid during exposure to the oxidant was not essential for cytoprotection [1,2]. Interestingly however, when cells were pre-incubated with neoechinulin A for 24 hours, and then exposed to MPP ϩ in fresh medium (without neoechinulin A), no cytoprotection was observed (data not shown).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…13,14) Previously, we found that neoechinulin A can protect neuronal PC12 cells from cytotoxicity due to oxidative/nitrosative stress induced by the superoxide/nitric oxide co-generator 3-morpholinosydnonimine (SIN-1). [13][14][15] Subsequently, we found that neoechinulin A can also protect PC12 cells from MPP ϩ by ameliorating downstream lethal events resulting from mitochondrial complex I inactivation.16) Although the cytoprotective mechanism of neoechinulin A remains unclear, it is probably not a single mechanism; while cytoprotection against SIN-1 can be afforded by pretreatment of cells with neoechinulin A at least for 12 h before SIN-1 challenge, 13) protection against MPP ϩ toxicity does not require pretreatment but its co-presence during the neurotoxin treatment.16)The present study was aimed at clarifying the cytoprotective mechanism of neoechinulin A in mitochondrial dysfunction-induced cell death. By using rotenone, we demonstrate here that neoechinulin A can also protect PC12 cells from rotenone cytotoxicity while paradoxically lowering cellular ATP levels.…”
mentioning
confidence: 99%